Structure of city councils in the Vilayet of Bosnia (1866-1875): between law and praxis - Krpić, Amir (Historical Thought, 2025)
This paper presents the composition of the city councils in the Vilayet of Bosnia between 1866 and 1875, from the provincial administration reform until the Herzegovinian uprising. An additional reason for choosing the year 1866 as the initial year is the fact that the yearbooks for the Vilayet of Bosnia started to be published in that year. The central questions of the paper are the religious and social affiliation of the city councils members, as well as the rate of implementation of the principle of electoral equality. Additionally, this paper aims to answer whether, and at what rate, the composition of the city councils in the Vilayet of Bosnia was in line with the 1871 law regulations.